A poor prognostic male choriocarcinoma with multiple systemic metastases: a case report and the literature review - Huang, Wenpeng; Zheng, Zuohuan; Bao, Zheng; Xiao, Xiaoyan; Li, Liming; Sun, Zhaonan; Kang, Lei (Frontiers in Medicine, 2024)
Background Non-gestational choriocarcinoma, also known as primary choriocarcinoma, is extremely rare in men, manifesting with specific signs such as breast feminization, testicular atrophy, and loss of libido. The presentation typically includes elevated serum β-hCG levels, widespread metastatic disease, and a rapid progression of the condition. Case report We present a rare case of a 41-year-old man diagnosed with choriocarcinoma, exhibiting a unique combination of multiple metastases, including lung, brain, bone, and retroperitoneal lymph node metastases, as confirmed by 18F-FDG PET/CT imaging. The patient was treated with aggressive chemotherapy and pembrolizumab, and the prognosis remained poor. The patient’s overall survival was a mere 5 months following diagnosis. Conclusion Non-gestational choriocarcinoma represents a rare entity in clinical practice and should be considered in young men presenting with gynaecomastia and elevated β-hCG levels alongside normal gonads. Thus, we advocate for a more comprehensive inquiry into medical history and a systematic examination. The 18F-FDG PET/CT examination not only visually delineates the lesion’s location and extent but also serves as a cornerstone for clinical tumor staging, providing valuable support for treatment monitoring and subsequent follow-up.